1997
DOI: 10.1126/science.277.5328.959
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Genetic Influence of CCR2 and CCR5 Variants on HIV-1 Infection and Disease Progression

Abstract: The critical role of chemokine receptors (CCR5 and CXCR4) in human immunodeficiency virus-type 1 (HIV-1) infection and pathogenesis prompted a search for polymorphisms in other chemokine receptor genes that mediate HIV-1 disease progression. A mutation (CCR2-64I) within the first transmembrane region of the CCR2 chemokine and HIV-1 receptor gene is described that occurred at an allele frequency of 10 to 15 percent among Caucasians and African Americans. Genetic association analysis of five acquired immunodefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
552
11
3

Year Published

1997
1997
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 819 publications
(591 citation statements)
references
References 45 publications
25
552
11
3
Order By: Relevance
“…CCR2-64I is common and found in 10% of Caucasians, 15% of African-Americans, 25% of Asians and 17% of Hispanics [50]. Epidemiologic studies by Smith et al first demonstrated the association of CCR2-64I with delayed HIV-1 disease progression [50], which was confirmed by most subsequent studies [73,98,99], but not by others [82,100,101]. CCR2-64I is not associated with reduced risk for HIV-1 infection [50].…”
Section: Variation In the Ccr2 Coding Regionmentioning
confidence: 95%
See 4 more Smart Citations
“…CCR2-64I is common and found in 10% of Caucasians, 15% of African-Americans, 25% of Asians and 17% of Hispanics [50]. Epidemiologic studies by Smith et al first demonstrated the association of CCR2-64I with delayed HIV-1 disease progression [50], which was confirmed by most subsequent studies [73,98,99], but not by others [82,100,101]. CCR2-64I is not associated with reduced risk for HIV-1 infection [50].…”
Section: Variation In the Ccr2 Coding Regionmentioning
confidence: 95%
“…Unlike the CCR5-32 allele that inactivated the major HIV-1 coreceptor, CCR2-64I causes a conservative change in a nonexposed portion of a coreceptor of questionable physiologic relevance [68,96,97]. CCR2-64I is common and found in 10% of Caucasians, 15% of African-Americans, 25% of Asians and 17% of Hispanics [50]. Epidemiologic studies by Smith et al first demonstrated the association of CCR2-64I with delayed HIV-1 disease progression [50], which was confirmed by most subsequent studies [73,98,99], but not by others [82,100,101].…”
Section: Variation In the Ccr2 Coding Regionmentioning
confidence: 99%
See 3 more Smart Citations